Global and Partitioned Multiprocessor Fixed Priority Scheduling with Deferred Pre-emption - Davis, Robert I. (2015)
This article introduces schedulability analysis for global fixed priority scheduling with deferred preemption (gFPDS) for homogeneous multiprocessor systems. gFPDS is a superset of global fixed priority pre-emptive scheduling (gFPPS) and global fixed priority non-pre-emptive scheduling (gFPNS). We show how schedulability can be improved using gFPDS via appropriate choice of priority assignment and final non-pre-emptive region lengths, and provide algorithms which optimize schedulability in this way. Via an experimental evaluation we compare the performance of multiprocessor scheduling using global approaches: gFPDS, gFPPS, and gFPNS, and also partitioned approaches employing FPDS, FPPS, and FPNS on each processor.